TRADISI PASAMBAHAN PADA MASYARAKAT MINANGKABAU (STUDI TENTANG PELAKSANAAN TRADISI PASAMBAHAN MANJAPUIK MARAPULAI DI DUSUN TAMPUAK CUBADAK, JORONG KOTO GADANG, NAGARI KOTO TINGGI, KECAMATAN BASO, KABUPATEN AGAM, SUMATERA BARAT) - Robi Fernandes; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Tradition pasambahan manjapuik marapulai is one type of Minangkabau oral literature. This tradition is carried on in traditional Minangkabau wedding ceremony. Pasambahan happens in the show is a kind of manjapuik marapulai pasambahan reciprocated. The study took place in the Dusun Tampuak Cubadak, Jorong Koto Gadang, Nagari Koto Tinggi, Baso, Agam, West Sumatra. The purpose of this study is to investigate the implementation of manjapuik marapulai pasambahan tradition is normative and the process of inheritance traditions manjapuik pasambahan marapulai. The method used in this research is descriptive qualitative research methods. Descriptive qualitative research is research that aims to uncover the facts, circumstances, and the various phenomena that occur. Relation to the disclosure of this research is the implementation of a normative tradition and shift implementation at this time. Therefore, the author will develop concepts, collect data and facts that occurred in the study area. Data collection techniques used were in-depth interviews and observation. While descriptive qualitative data analysis techniques through data collection, data reduction, data presentation and conclusion along with suggestions. Based on the implementation of the results of research, implementation pasambahan tradition manjapuik marapulai has happened persegeran of normative rules such as roles, responsibilities, and procedures for implementation. In the process of inheritance is also influenced by the level of interest or motivation, facilities and infrastructures, media information and communication, environmental conditions of society, and the media that are used during the process of inheritance. In the tradition of pasambahan manjapuik marapulai contained values such as the value of humility, value manners, the value of deliberation, the value of accuracy, and the value of adherence to customary rules applicable.Keywords: Tradition Pasambahan manjapuik marapulai, the implementation of the normative, and the process of inheritance